Procedural Results and Clinical Outcomes of Transcatheter Aortic Valve Implantation in Switzerland: An Observational Cohort Study of Sapien 3 Versus Sapien XT Transcatheter Heart Valves. (October 2015) - Binder, Ronald K.; Stortecky, Stefan; Heg, Dik; Tueller, David; Jeger, Raban; Toggweiler, Stefan; Pedrazzini, Giovanni; Amann, Franz W.; Ferrari, Enrico; Noble, Stephane; Nietlispach, Fabian; Maisano, Francesco; et al.
Abstract : Background—: New generation transcatheter heart valves (THV) may improve clinical outcomes of transcatheter aortic valve implantation. Methods and Results—: In a nationwide, prospective, multicenter cohort study (Swiss Transcatheter Aortic Valve Implantation Registry, NCT01368250), outcomes of consecutive transfemoral transcatheter aortic valve implantation patients treated with the Sapien 3 THV (S3) versus the Sapien XT THV (XT) were investigated. An overall of 153 consecutive S3 patients were compared with 445 consecutive XT patients. Postprocedural mean transprosthetic gradient (6.5±3.0 versus 7.8±6.3 mm Hg, P =0.17) did not differ between S3 and XT patients, respectively. The rate of more than mild paravalvular regurgitation (1.3% versus 5.3%, P =0.04) and of vascular (5.3% versus 16.9%, P <0.01) complications were significantly lower in S3 patients. A higher rate of new permanent pacemaker implantations was observed in patients receiving the S3 valve (17.0% versus 11.0%, P =0.01). There were no significant differences for disabling stroke (S3 1.3% versus XT 3.1%, P =0.29) and all-cause mortality (S3 3.3% versus XT 4.5%, P =0.27). Conclusions—: The use of the new generation S3 balloon-expandable THV reduced the risk of more than mild paravalvular regurgitation and vascular complications but was associated with an increased permanent pacemaker rate compared with the XT. Transcatheter aortic valve implantation using the newest generation balloon-expandable THV is associated with a low risk of stroke and favorable clinical outcomes. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01368250. Abstract : Supplemental Digital Content is available in the text.